International Conference on Engineering Tribology and Applied Technology : selected peer-reviewed full text papers from the 2nd International Conference on Engineering Tribology and Applied Technology (ICETAT 2020) : selected, peer reviewed papers from the 2nd International Conference on Engineering Tribology and Applied Technology (ICETAT 20), November 06-08, 2020, Chiayi, Taiwan - Hwang, Yunn-Lin (Advances in Science and Technology Ser., 2021)
Selected peer-reviewed full text papers from the 2nd International Conference on Engineering Tribology and Applied Technology (ICETAT 2020) Selected, peer-reviewed papers from the 2nd International Conference on Engineering Tribology and Applied Technology (ICETAT 20), November 06-08, 2020, Chiayi, Taiwan.